METHOD OF THE ESTIMATION OF FUNCTIONABILITY OF THE ELECTRONIC AUTOMATIC CONTROL SYSTEM THE OF AIRCRAFT POWER PLANT - N. N. Sirotin; K. N. Antonets (Научный вестник МГТУ ГА, 2016)
The paper deals with a new approach to an estimation of working capacity and quality of functioning of electronic system of an aircraft power-plant automatic control.